2007
DOI: 10.1590/s0004-28032007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas de pacientes pediátricos com constipação crônica de acordo com o grupo etário

Abstract: e Ulysses FAGUNDES-NETO 2 RESUMO -Racional -Não existem estudos avaliando as características clínicas de constipação de acordo com os grupos etários pediátricos.Objetivo -Avaliar as características da constipação crônica de acordo com o grupo etário. INTRODUÇÃOConstipação intestinal crônica é um problema freqüente na população pediátrica, estimando-se que seja a principal queixa em 3% das consultas de pediatria e 25% das consultas em ambulatórios de gastroenterologia pediátrica (8) . Em nosso meio, a prevalên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
2
2
5
Order By: Relevance
“…These results are not consistent with other studies regarding functional constipation during childhood, which report that this disorder has a similar prevalence in boys and girls [8]. We also identified a larger ratio of patients from urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are not consistent with other studies regarding functional constipation during childhood, which report that this disorder has a similar prevalence in boys and girls [8]. We also identified a larger ratio of patients from urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…The data obtained in São José dos Campos showed that the prevalence of constipation in females was higher after 14 years of age, which demonstrates the moment in adolescence that the increased prevalence of constipation in females begins; however, this increased prevalence was not sufficient to provide a significant difference in relation to male adolescents of the same age group. These data contrast those observed in specialized pediatric clinics, wherein severe constipation was observed to be more prevalent in the male gender [3,20]. Another interesting result is the observed higher occurrence of abdominal pain in adolescents with constipation (35.7%) in comparison to those without constipation (8.8%).…”
Section: Discussioncontrasting
confidence: 77%
“…Enterocolitis can progress to intestinal pneumatosis, perforation of the intestine and peritonitis. In addition, it can generate necrosis that will extend through the segments of the intestine, including the small intestine, and, consequently, may lead to death 18 . In summary, the most common symptom clusters are delayed meconium elimination, abdominal distension, vomiting and constipation 3,4 .…”
Section: Congenitalmentioning
confidence: 99%
“…Therefore, the objective of this study is to use the sensory properties of the denervated rectum by adding the motor activity that is absent by the juxtaposition of the healthy colon in a lateral-lateral anastomosis, thus assembling a tube in which the first half is formed by the rectum and the second half through the colon. As early as 1964, Franco Soave contributed with another surgical technique in which only the distal aganglionic mucosa is dissected and resected while a muscular tube through which the lymph node descends, thus avoiding lesions in the pelvic structures 18,21,22 .…”
Section: Surgical Techniques and Treatmentmentioning
confidence: 99%